Lateral setup error analysis of dosimetric impact for nasopharynx carcinoma using intensity modulated radiotherapy treatment - Syarifatul Ulya; Nuruddin Nasution; Wahyu Edy Wibowo; Supriyanto Ardjo Pawiro (Indonesian Association of Physicists in Medicine (AIPM/AFISMI), 2018)
Patients with nasopharyngeal carcinoma have been analyzed for lateral setup error. Systematic and randomized inter-fractional setup errors were evaluated in 48 patients with this case. Based on these errors, the margin was drawn from CTV to obtain the delineation of PTV structure, called PTV margin. MVCT system in tomotherapy has been used to get the number of error with four-degree direction setup. Moreover, the biggest error direction value was evaluated with in 6 patients and analyzed at D98 in each PTV and OARs. The result of PTV margin for the lateral, longitudinal, vertical, and rotation was 4.91 mm, 4.27 mm, 3.37 mm and 3.53 mm, respectively. According to the result of the PTV margin, a lateral direction showed the biggest value of error. So, achievable dose coverage of PTVs on the effect of the lateral shift were 87.04%, 60.19%, and 50% for 2, 4 and 6 mm, respectively. Furthermore, OAR dose in the right position is increasing with larger shift setup direction.